(untitled) (Journal of the Bangladesh Agricultural University, 2016)
Twenty parental genotypes of tomato were planted and observed of yield and yield attributing traits to measure genetic variability, character association and path coefficient analysis. Parent TM 371 ranked first with respect to yield (4.73 kg fruit yield per plant) followed by TM 390. In terms of average fruit weight TM 390 also was better performer. Analysis of variance for each trait showed significant differences among the genotypes. High genotypic and phenotypic coefficients of variation were recorded for fruits per plant, locule number per fruit and fruit yield per plant. Heritability was observed high for flowers per cluster, fruits per plant, fruit weight and fruit length. fruit per plant (52.30), followed by fruit weight (46.32).High heritability associated with high genetic advance was observed for fruits per plant (52.30) and fruit weight (46.32) and flower per cluster (33.50). Selection for such traits might be effective for the fruit yield improvement of tomato. Significant positive genotypic and phenotypic correlation was observed of fruits per plant, fruit weight, fruit diameter and locule number per fruit with fruit yield per plant indicated that selection strategies must be focus on these traits. Fruit diameter showed the highest positive direct effect (3.25) on fruit yield per plant followed by fruits per plant (1.54). Direct selection may be executed considering these traits as the main selection criteria to reduce indirect effect of the other characters during the development of high yielding tomato variety. J. Bangladesh Agril. Univ. 13(1): 65-69, June 2015